Description of Dental and Oral Health Maintenance Behavior of Pregnant Women at Bhayangkara General Hospital, Palu City, Central Sulawesi - Yufuai, Agustina R; Magfira, Magfira; Saputra, M.Khalid Fredy; Rahmadani, Nanang; Tahulending, Anneke A; Hermawan, Adi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Development in the field of dental and oral health is one part of overall health development which has a great responsibility towards increasing the value of dental and oral health status in the community. Dental health efforts need to be reviewed from environmental aspects, education, public awareness and dental health management, including prevention and treatment. In order to get good results, in dental health efforts it is necessary to know the problems associated with the process of tooth decay/caries. This study aims to determine the Behavioral Description of Dental and Oral Health Care for Pregnant Women at Bhayangkara General Hospital, Palu City. This study used a descriptive method with a cross-sectional design, namely direct observation and total sampling. According to the results of data collection, a sample of 30 people was obtained. The results of this study are that pregnant women brush their teeth in a day showing 1 time a day with a total of 19 people obtaining a percentage of 64%, for 2 times a day with a total of 7 people obtaining a percentage of 23%, and for 3 times a day with a total 4 people with a percentage of 13%. those who brushed their teeth every bath and shower in the afternoon with a total of 5 people got a percentage of 16%, those who brushed their teeth every time they wanted to sleep with a total of 4 people got a percentage of 13.3%, those who brushed their teeth before eating with a total of 15 people got a percentage of 50% and those who brushed Indeterminate teeth with a total of 6 get a percentage of 20%. The conclusion is that the behavior of maintaining dental health in pregnant women at Bhayangkara General Hospital, Palu City is still not good, seen from the frequency of brushing their teeth only once a day and the time to brush their teeth, namely before eating.